A Bivalent Protein r-PAbxpB Comprising PA Domain IV and Exosporium Protein BxpB Confers Protection Against B. anthracis Spores and Toxin - Majumder, Saugata; Das, Shreya; Somani, Vikas Kumar; Makam, Shivakiran S.; Kingston, Joseph J.; Bhatnagar, Rakesh (Frontiers in Immunology, 2019)
Anthrax vaccines primarily relying only on protective antigen (PA), the cell binding component in anthrax toxins provide incomplete protection when challenged with spores of virulent encapsulated Bacillus anthracis strains. Alternatively, formaldehyde inactivated spores (FIS) or recombinant spore components generate anti-spore immune responses that inhibit the early stages of infection and augment the PA protective efficacy. In the present study domain IV of PA was spliced with exosporium antigen BxpB via a flexible G4S linker to generate a single functional antigen r-PAbxpB that was further assessed for its protective efficacy against anthrax toxins and spore infection. Immunization of mice with r-PAbxpB elicited significantly high titer antibodies comprising IgG1:IgG2a isotypes in 1:1 ratio, balanced up-regulation of both Th1 (IL2, IL12, IFN-γ) and Th2 (IL4, IL5, IL10) cytokines and high frequencies of CD4+ and CD8+ T cell subsets. The anti-r-PAbxpB antibodies significantly enhanced spore phagocytosis, and killing within macrophages; inhibited their germination to vegetative cells and completely neutralized the anthrax toxins as evidenced by the 100% protection in passive transfer studies. Active immunization with r-PAbxpB provided 100 and 83.3% protection in mice I.P. challenged with 5 × LD100 LD of toxins and 5 × 104 cfu/ml Ames spores, respectively while the sham immunized group succumbed to infection in 48 h. Therefore, the ability of r-PAbxpB to generate protective immune responses against both spores and toxin and provide significant protection suggests it as an efficient vaccine candidate against B. anthracis infection.